The next Mrs. Blackthorne [a Bitter Creek novel] (New York Pocket Books, 2005)
A lavish summer wedding is being planned at Bitter Creek ranch. In one month, Clay Blackthorne will wed socialite Jocelyn Montrose. But when she hears stirrings of a corporate takeover by the family's archrival, North Grayhawk, Jocelyn covertly heads to North's ranch to offer a valuable commodity -- herself -- if North will call off his plans. Striking a deal to spend the summer with the steely, seductive North, Jocelyn fails to see that her sacrifice to protect the man she loves may have dire consequences.
Keywords: Conspiracies -- Fiction; Texas -- Fiction; Wyoming -- Fiction; Love stories; Romantic suspense fiction; Suspense fiction